ABNORMAL UTERINE BLEEDING IN ADOLESCENTS — ENDOCRINE PROFILE CONDITION - E. V. Sibirskaya; L. V. Adamyan; S. P. Yatsyk; I. F. Tin; S. G. Geras'kina (Вопросы современной педиатрии)
Aim: The purpose of the study was to evaluate the endocrine profile condition in adolescent girls with abnormal uterine bleeding. Patients and methods: The participants of the study were 110 adolescent girls in the age between 11 and 15 years taken to hospital by emergency indication in the period between 2010–2013 years with dysfunctional uterine bleeding for the term from 3 to 48 days. In the first day of hospitalization before starting the hormonal therapy all patients underwent the physical examination, ultrasonic examination of pelvic organs and endocrine profile assessment. Concentration of follicle-stimulating hormone (FSH) and luteinizing hormone (LH) and the levels of mammotropic hormone, thyrotropic hormone, estradiol, progesterone and testosterone in their blood were determined. Besides that physicians assessed the complete blood count indices: hemoglobin concentration, erythrocyte number and hematocrits. Results: It was determined that the predisposing causes of abnormal uterine bleeding development in adolescents: high somatic pathology frequency, abnormalities of neuroendocrinal system and menstrual cycle. Gynecological pathology in adolescents is represented by significant disorders of menstrual function establishment expressed in the later beginning of menstruation, its intensity and duration. The authors also note the higher frequency of inflammatory diseases such as adnexitis, edeitis, vulvovaginitis and coleitis in comparison with the control group (37.3 and 30%, respectively). Another tendency was observed while studying the endocrine profile: in patients with hyperestrogenism the normal or increased content of FSH at the normal or lowered LH concentration is observed. At the same time, in patients with hypestrogenism FSH concentration at the lower limits of the age group is lowered, while LH concentration is lowered or normal. Conclusion: Abnormal uterine bleeding in adolescents in the most cases is developing in the setting of relative hyper- or hypestrogenism and the clinical presentation of the condition depends on this indicator.